A települési vonzerők magyarországi megítélése = Assessment of the attractions of the residential place in Hungary - Koltai, Zoltán (Közép-Európai Közlemények, 2017)
We made a layered questionnaire survey in 2004-2005. In the research one thousand priváté persons responded to our questions. We wanted to find the answer to the following questions: what aspects do Hungárián citizens prefer when choosing their piacé of residence, which Hungárián cities are considered successful by the respondents and why, which are the cities that the stakeholders see as reál centres of gravity, how much are the respondents willing to move to another residential places? In the light of the results, we repeated our survey in 2012- 2013, allowing thereby the comprehensive evaluation of a period of almost ten years. In the second survey we used the method of a layered questionnaire survey again (the four aspects considered were as follows: breakdown of the Hungárián population by regions, gender, age groups and finally level of education), in which it was one thousand priváté persons again who responded to our questions. The number one attraction of settlements as residential places in Hungary is public safety now. This is followed by factors quite constant over a ten-year period like infrastructure of the settlement, the condition of the residential environment, the complexity of health Services, employment conditions, the presence of kindergarten and primary school education, transport relations and the possibilities of administration. It is still true that primarily the Hungárián big cities are considered as competitive and successful residential places. The proportion of answers specifying Budapest is outstandingly high and we can definitely say that the Hungárián Capital city is a separate category on its own within the Hungárián urban hierarchy. If we accept that the goal of competition is to enhance the well-being of the local residents, we can alsó say that the tool of successful participation in the competition is a special, bút flexibly modifiable development programme based on the partnership and operating in the coordination of local politics, businesses, the civil sector and the academic sphere; a development programme that the local stakeholders know and support as well.